Application of a Technofunctional Caseinate Hydrolysate to Replace Surfactants in Ice Cream. Issue 7 (1st April 2019) - Ewert, Jacob; Schlierenkamp, Felix; Fischer, Lutz; Stressler, Timo
Abstract: There is a demand for a clean label of ice cream in the food industry. To meet this requirement, alternative surfactants and hydrocolloids without an additive number have to be found. Here, a caseinate hydrolysate with improved interfacial properties was investigated as such an additive. Replacing only the surfactant resulted in ice cream characteristics, comparable to using a commercial emulsifier (INS 472b). Thus, a clean labeling of the surfactant using this hydrolysate is possible. By contrast, replacing the hydrocolloid additionally led to an unfavorable ice cream texture and stability. Abstract : Surfactants in ice cream have an additive number, perceived as unnatural by consumers. Hydrolysates can act as a replacer (clean label). This study investigates the application of a sodium caseinate hydrolysate with increased technofunctionality as an additive in ice cream, which results in a comparable product to ice cream with a commercial surfactant.